2021
DOI: 10.20870/oeno-one.2021.55.2.4570
|View full text |Cite
|
Sign up to set email alerts
|

Modeling malic acid dynamics to ensure quality, aroma and freshness of Pinot blanc wines in South Tyrol (Italy)

Abstract: Pinot blanc is a leading grapevine variety in South Tyrol (Italy) for wine production. The high quality of its wines derives from a typical aroma of elegant apple notes and lively acidity. The typicity of the final wine depends on the origin of the vine, the soil, the oenological practices and time of harvest. The South Tyrolean mountainous areas meet the cold climatic requirements of Pinot blanc, which guarantee its sweet-acidic harmony obtained when organic acids are in balance with the other components of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…Jones and Davis [36] found a similar effect of precipitation during flowering and the ripening period on the sugar concentration of Cabernet Sauvignon and Merlot varieties. Michelini et al [28] concluded that the DD-based model to predict the malic acid dynamics improved its performance adding other temperature-based parameters.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Jones and Davis [36] found a similar effect of precipitation during flowering and the ripening period on the sugar concentration of Cabernet Sauvignon and Merlot varieties. Michelini et al [28] concluded that the DD-based model to predict the malic acid dynamics improved its performance adding other temperature-based parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Besides sugar content, the acid content of grape juice is also a critical quality parameter since it affects wine quality [2]. Berry sugar accumulation and acid degradation are influenced by climatic variables, such as air temperature [27,28]. The non-linear regression analyses of SC and TA with heat accumulation (HA) calculated using the select models demonstrated that a high fraction of SC and TA variance was explained by the variation of these temperature-based indices (Table S6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations